Converting LDC export opportunities into business : a strategic response (ITC GenevaCH, 2001)
Draws lessons from successful entrepreneurs in LDCs and describes how to turn opportunities into effective business. Reviews the possibilities in 13 trade sectors of major potential for LDCs and looks at measures that can facilitate the creation of an enabling environment, including the range of trade support services that can help exporters improve their performance and increase their market competitiveness.
Keywords: EXPORT PROMOTION